Novel Peak-Source-Scanning (NPSS) Model for Thermal Control of Systems-in-Package (SiP) - Aziz Oukaira; Dhaou Said; Djallel Eddine Touati; Nader El-Zarif; Ahmad Hassan; Yvon Savaria; Ahmed Lakhssassi (IEEE Access, 2024)
One of the fast-growing electronic integration technologies in the modern high-density microelectronics industry is System-in-Package (SiP). It is expected to accelerate application development when reducing implementation risks with optimized codes. However, monitoring the thermal behavior of every chip in SiPs is challenging. This paper proposes a Novel Peak Source-Scanning (NPSS) algorithm based on the Gradient Direction Sensors (GDS) method. The proposed algorithm can detect and locate thermal peaks on any SiP. Detecting such peaks is vital for thermal monitoring and stress management on high-density semiconductor devices to avoid induced thermo-mechanical stresses. Furthermore, the NPSS algorithm can manage and monitor silicon chips with Multiple Heat Sources (MHS). To assess this algorithm, we used tools from COMSOL Multiphysics® and MATLAB® for Temperature-prediction (Tp), and Temperature-estimation (Te), respectively. Our simulations use the generalized GDS methodology for MHS using the finite element method (FEM) to highlight our NPSS capabilities to predict on-chip thermal peaks with a maximum error of 1.27 K (Kelvin).